If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying s + -3 = -5 Reorder the terms: -3 + s = -5 Solving -3 + s = -5 Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + s = -5 + 3 Combine like terms: -3 + 3 = 0 0 + s = -5 + 3 s = -5 + 3 Combine like terms: -5 + 3 = -2 s = -2 Simplifying s = -2
| 210.00+0.15x=322.50 | | 4-2=10 | | 3x=2+-1y | | 10x+9=27+7x | | f(-1)=5x+5 | | -(a+3)=-2(2x+3)-7 | | 2(t+2)=14 | | 81xsquared+8=0 | | f=-1 | | 41(x-6)+4=6x-8 | | 9x+7(3x-4)=7-5x | | 4x-2(x-3)=-5+4x+1 | | 9v-9=3(v-5) | | 2x^2+x^2=25*25 | | 4-2(x-3)=5+4x+1 | | 4x-15=x+51 | | 0.5x+9= | | 208=-13 | | 12x^3+28x^2+13x-45=0 | | 3x+10=7x-5 | | 25x^4-50x^3+25x^2=0 | | 8y+2=4x | | 3x+20=41 | | X+(-3)+9=-1+14 | | h(t)=-4.9t^2+24t+8 | | 4x^7-32x^5= | | 34+20=41 | | 2x-38=180 | | x^2+24-11x= | | 27=7+4w | | e^10x+6=12 | | 9a+27= |